Kolaborasi Mahasiswa KKN UNP Dengan Pemuda Pemudi Manganti Dalam Semarak Anak Desa - Alya Nurazizah; Faza Fadhilah; Mifta Hurrahmi; Tovana Naswa Berliana; Afiqah Khairunnisa; Anna Khairunnisa; Zuriva Deamala (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This research examines the collaboration between Padang State University (UNP) Community Service Program (KKN) students and young people in Jorong Manganti to enliven the Village Children's Day program. A qualitative approach was applied, using participatory observation and literature review, to capture the dynamics of interactions, roles, and challenges at each stage of the collaboration. Observations revealed that 12 students acted as primary facilitators and developed educational materials, while 20 local youth mobilized village children, adapted content to local wisdom, and provided supporting facilities. This structured collaboration, through three phases of joint initiation, integrated implementation, and collaborative evaluation, fostered a sense of ownership, high enthusiasm, and sustained program improvement. The literature review confirmed that synergy across groups of change agents enhances social inclusion and the sustainability of village innovations. In conclusion, the combination of academic methodology and local wisdom practices has proven effective in empowering children and adolescents, while the qualitative approach enriches understanding of the nuances of community interactions. Recommendations include event management training for young people, participatory discussion forums, multimedia documentation, further research, and the integration of quantitative and qualitative indicators for evaluating program effectiveness.